The earliest fortifications of the Peruvian south coast - Valdez, Lidio M. (My University, 2014)
From an archaeological perspective, warfare is a difficult issue to deal with in part due to its variability and in part because its material manifestation is not easily recognizable. However, a growing number of researchers argue that warfare often alters existing settlement patterns and settlements established amidst violence are regularly provided with human-made defensive barriers, named fortifications. Indeed, fortifications have been regarded as one of the most obvious indicators of violent conflict and are archaeologically highly visible. Here I present conclusive evidence to demonstrate that very early during the Early Intermediate Period (ca. 50 B.C.–A.D. 250) the first fortified settlements emerged in the Acari Valley of the Peruvian south-coast region. In addition to the fortifications, the layout of these settlements was carefully designed to obstruct invaders as well as to discourage potential attacks. In contrast to the evidence discussed here, similar evidence has not been reported for the valleys north of Acari, such as the Rio Grande and Ica valleys, in the heartland of the Nasca culture, thus making the Acari Valley the location of the earliest fortified settlements of the entire south-coast region.
Keywords: warefare; fortifications; Acari; Peru